Factors Influencing Community Participation in Waste Management in the Climate Village Program of RW 8, Lesanpuro Subdistrict - Gusni Amalia Vianti; Alfatiha Dinda Meiril; Lailia Yuslichati Rahmadani; Nilam Permatasari (PANGRIPTA, 2026)
Unmanaged waste can generate significant environmental impacts, including contributing to global warming. Therefore, effective waste management is essential to reduce waste accumulation at Final Disposal Sites. In the context of household waste, the active participation of the community in waste management is a crucial decision. Through the Climate Village Program initiated by the Ministry of Environment and Forestry, RW 8 Lesanpuro has implemented community-based waste management. The implementation of the Climate Village in Malang City is an important effort to encourage community behavioral changes toward more sustainable environmental management, especially in waste management. This study aims to identify the factors influencing community participation along with their probability values. This study employed in-depth interviews as the data collection method, using a random sampling technique, and the data were subsequently analyzed using binary logistic regression. The novelty of this study lies in the analysis of factor influencing community participation at micro scale in the Climate Village area, which has received limited attention in previous studies. The results indicate that motivation and perception are the primary factors influencing community participation. Participation is estimated to reach 95.89% if both factors are present within the community group. Furthermore, this study offers valuable insights for improving the participation of RW 8 residents in waste management as a form of environmental sustainability. Moreover, the findings of this study may serve as a reference for optimizing community participation in waste management on a larger scale, such us at the city level.